Brand Betrayal: A Comprehensive Study to Examine the Indicators and Consequences of Brand Betrayal Towards Consumer Behavior - Rehmat, Sana; Wasim, Manahil (Archives of Business Research, 2021)
Abstract Brand betrayal is induced by the brand itself when it fails to fulfill its promised moral obligations and involves the type of behavior that fractures the strong self–brand connection with the consumers. Brand managers must come across several negative types of consumer behaviors that depict their sense of dissatisfaction. Additionally, the effort of a brand to reduce the effects of brand betrayal is reflected by the sheer amount of customer apologies and compensation paid to the affected consumers. Having a sound knowledge about the primary indicators of brand betrayal encourages the brand managers to take necessary measures to deal with the challenges of the negative consumer-brand relationship. The resultant revenge behaviors depicted by the consumers include different types of activities such as spreading negative word-of-mouth and avoiding the brand itself, customer incivility, etc. The existing literature on the consequences of brand betrayal is insufficient to build the novel theory around the construct and differentiate it from brand dissatisfaction. The current research in brand dissatisfaction argues that it is a more generalized construct than brand betrayal that becomes the immediate cause of brand avoidance. The effect of these consequences needs to be addressed by the marketing theorists and practitioners to strengthen the consumer-brand relationship and manage the longer-lasting results of negative consumer behaviors.